PERAN DAN KEDUDUKAN PEMERINTAH DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI INDONESIA - Nurul amaliyah; Tarwillah; Suraijiah (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2026)
In essence, Islamic education aims to build and advance human potential. This potential includes physical and spiritual potential such as reason, emotion, will, and many other potentials. Talking about government in Islam, at least we will come across the terms State, Ruler and Islamic government strategy which are integrated into the government system. A nation needs a ruler to regulate all interests in it. A nation will live with full order and order, working together shoulder to shoulder in building its nation. With the existence of a government system, a nation tends to be easy to develop and of course will be the initial capital for the development of its country even better. This research is a qualitative research using libraries. The data were obtained from writing on Islamic literature which was then analyzed and described descriptively. The government has a very important role in Islamic education, both in terms of policy and provision of resources. Likewise, the position of the government in Islamic education is as a facilitator and supervisor who tries to ensure that Islamic education can run well and provide benefits to the entire community. In addition, the government is also responsible for maintaining Islamic education relevant to the development of the times and able to contribute to forming the character of a nation that is noble and knowledgeable.